Enhancing student competencies through DataCamp: Python Programming Workshop at FSKM - Sa'dan, Siti 'Aisyah; Mohd Rick, Abd Malik; Mat Tahir, Norazuwin Najihah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The DataCamp: Python Programming Workshop, organized by the Faculty of Computer and Mathematical Sciences (FSKM), UiTM Negeri Sembilan Branch, was held on 13 and 20 June 2025 at Labs 1 and 2, FSKM. The workshop aimed to introduce students to the fundamentals of Python programming through an interactive and practical learning approach. As one of the most widely used programming languages, Python was highlighted for its applications in data analytics, machine learning, artificial intelligence, and modern system development. The program sought to enhance students’ programming skills while exposing them to technology-driven career opportunities.